Free Press, Fair Trial Data, 1970 - Nagel, Stuart S. ([Verlag nicht ermittelbar], 1984)
This data collection contains information gathered in a 1970 survey of 623 newspaper editors, police chiefs, bar associations, prosecuting attorneys, and defense attorneys from a sample of 166 cities across the country. The study's research objectives were to develop a model for determining the optimum mix of free press and fair trial in pending criminal cases, to compare alternative procedures for handling the free press/fair trial problem, and to compare the attitudes and procedures of the various decisionmakers involved. Information gathered in the survey includes: (1) the degree of pretrial press publicity allowed on pending criminal cases, (2) relevant attitudes and opinions, especially concerning ways of reducing the adverse effects of pretrial publicity while still having an informed public (e.g., the degree to which the public needs to know the details of criminal proceedings, whether the traditional legal remedies of change of venue, voir dire, sequestering, etc., are adequate to neutralize the effects of possibly prejudicial news coverage, and whether the American Bar Association's restrictions on the extent of information lawyers can release represents an infringement upon the people's right to know), (3) the benefits seen as derived from news coverage of criminal cases, and (4) prevailing pretrial procedures by editors, police, prosecutors, defense attorneys, and judges. Demographic data (e.g., population, region, and whether an SMSA or not) about the 106 cities represented in the survey are also included in the file.